'The Music was Speaking to Me': Using narrative inquiry to describe sacred moments with music. (July 2022) - Griffith, Frances J.; Wong, Serena; Dietrich, Kelsey M.; Exline, Julie J.; Pargament, Kenneth I.
Abstract: Sacred moments, or sanctified periods of time, may result in psychological benefits for those who experience them, and music may have the potential to facilitate or enhance these sacred moments. Using qualitative content analysis, the present study examined narratives from US adults ( N  = 209) who had experienced important moments while listening, playing, composing, or otherwise interacting with music and who perceived this moment to be sacred to some degree. Our research questions focused on the types of music associated with sacred moments, the features of these sacred moments, and the contexts of these sacred moments with music to determine the nature of these moments experienced by the general public. There was a diversity of music genres associated with sacred moments, the largest group described engaging with rock music, and most people were familiar with the musical piece. Most participants recounted that they were listening to recordings rather than live music or performing themselves. The largest group of participants described that they were at their home or that of a loved one, many with friends or family and others alone. Many participants described that they were forming or maintaining relationships during these moments, feeling joy, and/or thinking about their interconnectedness with others. Over half of participants described that the moment gave them a new perspective or purpose. The implications of these findings for the study of sacred moments and therapeutic practice incorporating spirituality are discussed. Highlights: We analyzed content of participant narratives of sacred moments ( N  = 209) with music. The largest group were listening to rock music and were familiar with the music. Many described they were home, alone or with friends or family, during the moment. Many recalled they were feeling joy and interconnectedness and forming relationships. Over half of participants described the moment gave them a new perspective or purpose.